The relationship between active and passive Facebook use, Facebook flow, depression symptoms and Facebook Addiction: A three-month investigation - Julia Brailovskaia; Jürgen Margraf (Journal of Affective Disorders Reports, 2022)
Background: The present study investigated the link of active and passive Facebook use, Facebook flow and depression symptoms with Facebook Addiction (FA). Methods: Data of 127 German Facebook users (Mage (SDage) = 25.10 (7.03), range: 18–58) were assessed at two measurement time points over a period of three months (first measurement = T1, second measurement = T2) via online surveys. Results: FA (T2) was significantly positively linked to active Facebook use (T1), Facebook flow (T1) and depression symptoms (T1). Its relationship with passive Facebook use (T1) was non-significant. Facebook flow (T1) positively mediated the association between active Facebook use (T1) and FA (T2). In contrast, active Facebook use (T1) did not serve as a mediator between Facebook flow (T1) and FA (T2). Limitations: Given the non-experimental design of the present study, only hypothetical conclusions on causality can be drawn. Conclusions: Current results demonstrate that active Facebook use could contribute to the experience of flow that serves as an antecedent of FA. This is particularly relevant for individuals with enhanced depression symptoms. The findings should be made a subject of discussion in education and prevention programs, and in therapeutic context.